INVESTIGATING LOW ATTENTION SPAN IN KINDERGARTEN 3: A CASE STUDY AT SCHOOL XYZ [PENYELIDIKAN RENDAHNYA RENTANG PERHATIAN DI TAMAN KANAK-KANAK 3: SEBUAH STUDI KASUS DI SEKOLAH XYZ] - Tania Theresia Manalu; Yonathan Winardi (Polyglot: Jurnal Ilmiah)
The attention span of early childhood children is a critical factor in forming their developmental foundation, encompassing physical, cognitive, social, and emotional growth. Informal interviews with classroom teachers reveal that students struggle to maintain attention during instruction, often displaying behaviors such as restlessness and lack of focus immediately after the lesson begins. This thesis aims to investigate the impact of internal and external factors on the attention span among Kindergarten 3 students at Sekolah XYZ, focusing on regular classroom settings and specialized classes (music and art). This research employs a case study method by combining observations, interviews, and documentation to provide a comprehensive understanding of the issue. The findings of this research include a limited direct exploration within the classroom and the type of curriculum currently used, which are reasons for the low attention span of Kindergarten 3 students. This study highlights the novelty of tactile learning approaches to enhance attention span. To expand these findings, future research is expected to consider comparative studies across Yayasan XYZ network, investigating the impact of direct exploration and different educational approaches on the attention and learning outcomes of students in specialist classes.